2014
DOI: 10.1128/aac.03469-14
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Abacavir in Pregnant Women

Abstract: e For the first time, a population approach was used to describe abacavir (ABC) pharmacokinetics in HIV-infected pregnant and nonpregnant women. A total of 266 samples from 150 women were obtained. No covariate effect (from age, body weight, pregnancy, or gestational age) on ABC pharmacokinetics was found. Thus, it seems unnecessary to adapt the ABC dosing regimen during pregnancy.A bacavir (ABC) is a potent nucleoside reverse transcriptase inhibitor administered to treat human immunodeficiency virus (HIV) inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Typically 1‐2 samples per dosing interval are collected from each patient for PK analysis. Fauchet et al used a population PK approach to describe abacavir PK in HIV‐infected pregnant women (n = 36) with 1‐2 samples collected per patient . Zheng et al reported tacrolimus maternal blood concentrations using 1 sample per patient, which was collected at the time of delivery .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Typically 1‐2 samples per dosing interval are collected from each patient for PK analysis. Fauchet et al used a population PK approach to describe abacavir PK in HIV‐infected pregnant women (n = 36) with 1‐2 samples collected per patient . Zheng et al reported tacrolimus maternal blood concentrations using 1 sample per patient, which was collected at the time of delivery .…”
supporting
confidence: 90%
“…Fauchet et al used a population PK approach to describe abacavir PK in HIV-infected pregnant women (n ¼ 36) with 1-2 samples collected per patient. 17 Zheng et al reported tacrolimus maternal blood concentrations using 1 sample per patient, which was collected at the time of delivery. 18 Our study also adopted a sparse sampling strategy that allowed us to coordinate the study visit with regularly scheduled prenatal visits.…”
mentioning
confidence: 99%
“…Because the mRNA seems to correlate with ENT1 function, as evidenced in pharmacoresistance studies (Giovannetti et al, 2006;Marcé et al, 2006;Tsujie et al, 2007;Eto et al, 2013), we hypothesize that the observed placental mRNA variability might be reflected in protein/function level. Therefore, it may represent a potential reason for differences in reported cord-to-maternal blood concentration ratios (Chappuy et al, 2004;Best et al, 2006;Fauchet et al, 2014).…”
Section: Downloaded Frommentioning
confidence: 99%
“…nih.gov/contentfiles/lvguidelines/PerinatalGL.pdf). Transplacental transfer of abacavir in humans has been investigated only sparsely, and its cord-to-maternal-blood concentration ratio is variable, ranging from 62% to 163% at term (Chappuy et al, 2004;Best et al, 2006;Fauchet et al, 2014). The pharmacokinetics of antiviral drugs are frequently affected by the activity of drug transporters (Kis et al, 2010;Neumanova et al, 2014Neumanova et al, , 2015Neumanova et al, , 2016Ceckova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among these women, 88% had a third‐trimester abacavir exposure similar to that reported in nonpregnant patients. A subsequent population pharmacokinetic analysis of abacavir, which included 266 samples from 36 pregnant and 114 nonpregnant women, also estimated that abacavir pharmacokinetics were unchanged during pregnancy and were not influenced by any studied covariate (age, body weight, pregnancy, and gestational age) . Based on these findings, no dosage adjustment of abacavir is recommended during pregnancy…”
Section: Nucleoside/nucleotide Reverse Transcriptase Inhibitorsmentioning
confidence: 99%